Living in Sarawak - Invernizzi, Luca.; Ong, Edric (London : Thames and Hudson, 1996)
Sarawak is an East Malaysian state located on the island of Borneo. This book shows the dual influences of tradition and change found in its architecture and decorative arts. It includes glimpses into the interiors of private homes, from contemporary houses to centuries-old longhouses.
Originally published as: Sarawak style. Singapore : Times Editions, 1996.
Keywords: Art -- Malaysia -- Sarawak; Architecture -- Malaysia -- Sarawak; Decorative arts -- Malaysia -- Sarawak; Sarawak -- Civilization